L’incontro prudente, poesia e filosofia - Papi, Fulvio (Bollettino Filosofico, 2017)
Each contemporary poetry has, in its own composition, a symbolic level that selects the poetical “I” from the living I, giving value to its own poetical experience. Poetry has very different embodiments. This dissemination of poetry raises the problem of a good comprehension that has to exclude any reference to an essence. The poetical object makes it necessary to have different perspectives: biographical, historical-social, psychoanalytical, linguistic and formal ones. Only poetical experience makes it possible to understand them.